PANAS GAS BUANG MESIN DIESEL UNTUK TAPIOKA - Anam, Khoirul (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
Drying technique plays a very important role in determining the quality and continuity of the tapioca flour manufacturing process. Traditionally the drying process is carried out by farmers by utilizing the sun's heat, but problems occur when the rainy season comes while production must continue to meet needs. which requires a large area of land and is very dependent on the weather with a lot of hot sun. Based on the analysis of the results of data processing using the Taguci experimental method to determine the optimum design of the main dimensions of the economizer in the laundry factory, the following conclusions are obtained. Effect of tube diameter, lay out, pitch ratio and excess area on the economizer Tube diameter (dO) has a significant effect on the amount tube and shell diameter (Ds).Picth ratio (PR) has a significant effect on shell diameter (Ds) but has no significant effect on the number of tubes. Excess area has a significant effect on the number of tubes but has no significant effect on shell diameter (Ds).Lay out has the same effect on shell diameter and tube number. Optimum economizer conditions. Optimum tube number ( Nt ) is obtained from a combination of tube diameter ( do ) 0.0254 m, excess area (PR) 1.2 , lay out 30o and pitch ratio 1 ,2. The optimum shell diameter is obtained from a combination of tube diameter (do) 0.0381 m, pitch ratio (PR) 1.2, excess area 1.2 and lay out 30o.Keywords: Dryer, Shell Diameter, Tube Diameter